REALIZING SUSTAINABLE WELFARE OF MUSTAHIK THROUGH OPTIMIZING ZAKAT MANAGEMENT AT BAZNAS BUNGO REGENCY - Budi, Agung Setia; Zaki, Muhammad; Asmoro, Endang Dwi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study focuses on optimizing zakat management at BAZNAS Bungo Regency to realize sustainable welfare for Mustahik through the productive zakat program. The purpose of this study is to analyze the role of the productive zakat program in improving the welfare of mustahik in a sustainable manner, as well as to identify obstacles faced in the collection, distribution, and empowerment of mustahik. This study uses a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation at the BAZNAS Bungo Regency. The results of the study indicate that although the productive zakat program has been running, there are still challenges in monitoring and mentoring mustahik and limitations in the application of technology to support zakat management. This study also found that closer collaboration between BAZNAS and the local Government is not just beneficial, but crucial for the optimal empowerment of mustahik. The implications of this study are the importance of strengthening monitoring and evaluation strategies and increasing the use of technology to improve the effectiveness of zakat management. In addition, closer collaboration is needed between zakat institutions and local governments to support the empowerment of mustahik more optimally and sustainably.